PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PEMASARAN MELALUI MEDIA SOSIAL TERHADAP MINAT BELI PRODUK SMARTPHONE IPHONE DI KECAMATAN MARGA KABUPATEN TABANAN - Ni Putu Tya Rumala Sari; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
There are many factors that encourage and are taken into consideration by consumers in terms of consumer buying interest which is always changing and is more likely to follow developing trends. Social media users such as Instagram, Facebook and Tokopedia are places where iPhone smartphone products are used to display their products on the internet. This research aims to determine the influence of leather products, price perceptions and social media marketing on interest in purchasing smartphone iPhone products in Marga District, Tabanan Regency. The population in this study is iPhone smartphone product users in Marga District, Tabanan Regency, the number of which is not known for certain. The technique used by the research in selecting the sample was nonprobability sampling, so the number of samples used was 97 respondents. The data analysis technique used to answer the hypothesis is multiple linear regression analysis. The results of this research show that product quality has a positive and significant effect on interest in purchasing Smartphone iPhone products in Marga District, Tabanan Regency. Price perception has a positive and significant effect on interest in purchasing Smartphone iPhone products in Marga District, Tabanan Regency. Social marketing media has a positive and significant effect on interest in purchasing Smartphone iPhone products in Marga District, Tabanan Regency.